Intracerebral tuberculoma in children with tuberculous meningitis - Altunbaşak, Şakir; Alhan, Emre; Baytok, Vildan; Aksaray, Necmi; Önenli, Neslihan (The Turkish Journal of Pediatrics, 1996)
Not all patients with tuberculosis develop tuberculoma during the disease or anti-tuberculous therapy. Therefore, we compared various parameters in patients with and without tuberculoma and presented the results. We formed two groups from the patients with tuberculous meningitis: Group I consisted of 18 patients with tuberculoma, and Group II consisted of 18 randomly selected patients without tuberculoma. Significant difference between the groups was found with respect to level of consciousness and CSF-glucose level (p<0.05). The consciousness level was more depressed and the CSF-glucose level more decreased in the group without tuberculoma. These findings were discussed.